Lactobacillus plantarum Isolates from Homemade Dahi as a Potential Probiotic with In vitro a-amylase Inhibitory Activity - Ranjan K. Tirwa; Buddhiman Tamang; Lalit K. Chaurasia (Journal of Pure and Applied Microbiology, 2020)
Postprandial hyperglycemia (PPG) is among the earliest signs related to type 2 diabetes. Targeting the α-amylase enzyme responsible for the initial stage of carbohydrate digestion can be an effective strategy to control the PPG. With this objective, about 300 Lactic acid bacteria were obtained from different ethnic fermented foods of Sikkim and screened for α-amylase inhibitor (AAI) activity. Five isolates of Lactobacillus (Lb.) plantarum were found to inhibit α- amylase whose inhibitory potential was similar to that of copper sulfate and acarbose. Maximum AAI activity was observed within 24 hours of incubation. All the isolates were also assessed for other probiotic properties including bacterial adherence to hydrocarbons, utilization of prebiotic components, etc. Among the safety features of the isolates tested, none of the isolates was hemolytic and neither could hydrolyze gelatin. Most of the isolates were sensitive to ampicillin, chloramphenicol, and erythromycin out of twelve antibiotics tested. These isolates also showed good response to in vitro simulation of oro-gastric-intestinal transit which confirms its ability to survive in the gastrointestinal tract. Therefore, these Lb. plantarum isolates can be potential probiotic candidates with a- amylase inhibitory activity which can be further exploited for the management of postprandial hyperglycemia.